Sibling group size and BMI over the life course: Evidence from four British cohort studies. (September 2022) - Chanfreau, Jenny; Barclay, Kieron; Keenan, Katherine; Goisis, Alice
Abstract: Only children, here defined as individuals growing up without siblings, are a small but growing demographic subgroup. Existing research has consistently shown that, on average, only children have higher body mass index (BMI) than individuals who grow up with siblings. How this difference develops with age is unclear and existing evidence is inconclusive regarding the underlying mechanisms. We investigate BMI trajectories for only children and those with siblings up to late adolescence for four British birth cohorts and across adulthood for three cohorts. We use data on BMI from ages 2–63 years (cohort born 1946); 7–55 years (born 1958); 10–46 (born 1970) and 3–17 years (born 2000–2002). Using mixed effects regression separately for each cohort, we estimate the change in BMI by age comparing only children and those with siblings. The results show higher average BMI among only children in each cohort, yet the difference is substantively small and limited to school age and adolescence. The association between sibling status and BMI at age 10/11 is not explained by differential health behaviours (physical activity, inactivity and diet) or individual or family background characteristics in any of the cohorts. Although persistent across cohorts, and despite the underlying mechanism remaining unexplained, the substantively small magnitude of the observed difference and the convergence of the trajectories by early adulthood in all cohorts raises doubts about whether the difference in BMI between only children and siblings in the UK context should be of research or clinical concern. Future research could usefully be directed more at whether only children experience elevated rates of disease, for which high BMI is a risk factor, at different stages of the life course and across contexts. Highlights: Only children in four UK cohorts have higher average BMI than those with siblings. Difference in BMI is substantively small and limited to school age and adolescence. Association at age 10/11 is not explained by health or social characteristics. BMI trajectories of only children and siblings converge by early adulthood.